Efficacy of Clove Oil (Syzygium aromaticum) as a Natural Anaesthetic at Various Doses on the Survival Rate of Fighting Fish (Betta sp.) During Closed Transport - Furqon Saeful Rohman; Didik Budiyanto; Maria Agustini (Universitas Islam Lamongan, 2026)
Fighting fish (Betta sp.) is a popular ornamental fish with high economic value, requiring special handling during maintenance, transportation, or medical procedures to prevent stress and injury. However, concerns about their negative impacts on human health, the environment, and potential residues in fishery products have led regulatory bodies to restrict or prohibit their use. In Indonesia, the Ministry of Marine Affairs and Fisheries through Regulation No. 1/PERMEN-KP/2019 has officially categorised MS-222 as a restricted veterinary pharmaceutical substance, thereby driving the aquaculture industry to seek safer and more sustainable alternatives. Therefore, a safe natural anaesthetic alternative is needed, such as clove oil containing eugenol. This research is important to study the effectiveness of clove oil as a natural anaesthetic for fighting fish, to provide a safe, effective, and environmentally friendly guide for cultivators and entrepreneurs. This research used a Completely Randomized Design (CRD) method with 4 different clove oil doses (0.1 ml, 0.2 ml, 0.3 ml, and 0.4 ml) and 6 replications, where each plastic contained 100 ml of water, 1 fighting fish, and oxygen, was sealed with a rubber band, placed in a styrofoam box, and simulated for an 8-hour journey. The results showed that the administration of different clove oil doses significantly affected the survival rate of fighting fish (Betta sp.) in closed transport (p < 0.05). The optimal dose identified was 0.1 ml per 100 ml of water, with the highest survival rate reaching 96.67%. This dose resulted in an induction time of 29.83 minutes, an anaesthesia duration of 265.00 minutes, and a recovery time of 25.17 minutes, and showed no negative impact on water quality parameters during transport.